Association of peak factor VIII levels and area under the curve with bleeding in patients with haemophilia A on every third day pharmacokinetic‐guided prophylaxis. (1st March 2016) - Valentino, L. A.; Pipe, S. W.; Collins, P. W.; Blanchette, V. S.; Berntorp, E.; Fischer, K.; Ewenstein, B. M.; Oh, M.; Spotts, G.
Abstract : Introduction: We previously showed that pharmacokinetic‐guided prophylaxis (PKP) allows the dosing interval to be extended while maintaining a specific trough level. However, the associations of peak factor VIII (FVIII) levels and area under the curve (AUC) with breakthrough bleeding have not been investigated. Aim: The aim of this study was to analyse data from the PKP arm to determine whether peak FVIII levels, AUC and time with FVIII levels in a haemostatically effective range are independent predictors of bleeding during prophylaxis. Methods: Post hoc analysis of the association of FVIII levels and AUC with annualized bleeding rate in 34 patients on PKP. Results: During 1 year of PKP, 131 bleeding episodes occurred in 24/34 patients. Average peak FVIII levels ranged from 24 to 168 IU dL −1, with higher values associated with a decreased risk for all bleeding (joint and non‐joint; P < 0.01) and joint bleeding ( P < 0.01). Following rFVIII infusion, median percent of time spent with FVIII levels >20 IU dL −1 was 22%; median AUC was 1363. Both values were significantly associated with a lower ABR when targeting a 1% trough at 72 h. Conclusion: When PKP was administered every third day, higher peak FVIII levels, higher AUC and more time spent per week with FVIII levels >20 IU dL −1 provided increased protection from joint and non‐joint bleeding. These data highlight the potential impact of variability in individual pharmacokinetic and bleeding risk and support the need for high peak levels and AUC in some patients treated every third day. The findings do not necessarily apply to alternate‐day or other prophylactic dosing regimens.